The exile: the flight of Osama Bin Laden - Scott - Clark Cathy (Bloomsbury Publications, 2018)
The Exile charts the frantic attack on Afghanistan by the United States in their hunt for Bin Laden; the formation of ISIS; the development of the CIA's torture programme; Iran's secret shelter for Bin Laden's family and al-Queda leaders; and the power struggles, paranoia and claustrophobia within the Abbottabad house prior to "Zero Dark 30" and the raid. A landmark work of investigation and reportage, The Exile is essential reading for anyone concerned with history, security and future relations with the Islamic World.